Confidence in Public Institutions and the Run up to the October 2019 Uprising in Lebanon - Ali Fakih; Paul Makdissi; Walid Marrouch; Rami V. Tabri; Myra Yazbeck (Institute of Labor Economics (IZA), 2020)
This paper uses the 2013 World Value Survey, as well as the 2016 and 2018 waves of the Arab Barometer, to analyze the dynamics of trust in public institutions in Lebanon. It finds strong evidence that confidence in most public institutions has decreased between 2013 and 2016. The evidence of this decrease is robust to the numerical scale assigned to the different ordinal categories of trust and to assumptions on the missing values generating process. This finding highlights the importance for policymakers in developing countries to survey the perceptions and political attitude of their constituents in order to improve the performance of public institutions.
Keywords: D72; O53; P16; P40; 330; confidence; institutions; uprising; ordinal variable